Fourteen candidate RR Lyrae star streams in the inner Galaxy. Issue 3 (14th November 2017) - Mateu, Cecilia; Read, Justin I; Kawata, Daisuke
Abstract: We apply the GC3 stream-finding method to RR Lyrae stars (RRLSs) in the Catalina survey. We find 2 RRLS stream candidates at >4σ confidence and another 12 at >3.5σ confidence over the Galactocentric distance range 4 <  D /kpc < 26. Of these, only two are associated with known globular clusters (NGC 1261 and Arp2). The remainder are candidate 'orphan' streams, consistent with the idea that globular cluster streams are most visible close to dissolution. Our detections are likely a lower bound on the total number of dissolving globulars in the inner galaxy, since many globulars have few RRLSs, while only the brightest streams are visible over the Galactic RRLS background, particularly given the current lack of kinematical information. We make all of our candidate streams publicly available and provide a new galstreams python library for the footprints of all known streams and overdensities in the Milky Way.